2019
DOI: 10.17222/mit.2018.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subzero treatments on the mechanical properties of the SAE 4140 steel

Abstract: In this study, effects of holding in liquid nitrogen and cryogenic methods applied onto the SAE 4140 steel were empirically investigated. In this context, austempering, holding in liquid nitrogen, the conventional cryogenic process and tempering processes were applied in different orders and combinations. The temperature of the samples to be tempered in liquid nitrogen was decreased from room temperature to-196°C at the average rate of 1.6°C/min and held at this temperature for 24 h. The temperature of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Cryogenic temperature or holding time with different values is mostly considered in the cryogenic treatment of steel in literature. Menderes et al [20] investigated the effect of cryogenic treatment for different holding times (12 h, 24 h, 36 h, and 48 h) at −140°C on mechanical properties of AISI 4140 steel and found that tensile strength improved by 10% and hardness by 5% after cryogenic treatment and the optimum holding time of cryogenic treatment was 36 h. Senthilkumar et al [21][22][23] found that cryogenic treatment improved hardness and wear resistance of AISI 4140 steel as well as compressive residual stress, and wear resistance of the steel improved more after cryogenic treatment at −196°C for 24 h than for 12 h and 18 h. HÖKE et al [24] reported that SAE 4140 steel had an improvement in microhardness and toughness after cryogenic treatment at −140°C for 24 h. Sahin et al [25] studied the effect of different cryogenic temperatures (−140°C and −196°C) for 24 h on SAE 4140 steel and found that hardness slightly increased, which was attributed to the transformation of retained austenite to martensite. Jamali et al [26] showed that cryogenic treatment could increase hardness, tensile strength, and impact toughness of AISI 4140 steel, and transformation of retained austenite to martensite and carbide precipitations were responsible for the improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic treatment consists of three stages: cooling down to a cryogenic temperature, holding for a period of time and heating up to ambient temperature, and the following influencing parameters are apparently involved in these stages: cooling rate, cryogenic temperature, holding time, heating rate and cycles (number of treatments), which are varied with different materials in different research studies. in most studies, cooling and heating were generally controlled at a slow rate to avoid thermal shock that may result in cracking in microstructure of materials [30,41,[51][52][53][54][55], and in addition, the practical cooling and heating rates are mainly around 0.2-2.5°C/min [23,24,35,[38][39][40][41][48][49][50][51][52][53][54].…”
Section: Cryogenic Treatmentmentioning
confidence: 99%
“…Zhirafar et al [50] revealed that cryogenic treatment improved hardness of AISI 4340 steel due to transformation of retained austenite to martensite. Sahin et al [51] studied effect of cryogenic treatment on mechanical properties (excluding wear resistance) of SAE 4140 steel at two different cryogenic temperatures (−140°C and −196°C) in liquid nitrogen for 24 h and found that hardness increased by 0.7% or 1.0% respectively, which was explained with the transformation of retained austenite to martensite. However, in the literature, cryogenic treatment parameters of cryogenic temperature and holding time were separately considered rather than fully considered, and the parameter of cycles was not involved, to the author's knowledge.…”
Section: Introductionmentioning
confidence: 99%